University flags posted at half-staff as tribute to Pres. Kennedy - Uribes, Tom::::::::: (2013)
As proclaimed by President Obama, Fresno State will observe the Day of Remembrance for President John F. Kennedy , by flying the university's flags at half-staff on Nov. 22 until sunset.